STRATEGI INOVATIF PENGELOLAAN KEUANGAN PAUD BERBASIS GOOD FINANCIAL GOVERNANCE DALAM MEWUJUDKAN TRANSPARANSI DAN AKUNTABILITAS - Anna Nadha Khilma Inthaha; Siti Arrum Apriliyani; Rahmiati Rahmiati; Fetty Ernawati (EDUKIDS : Jurnal Inovasi Pendidikan Anak Usia Dini, 2026)
ABSTRACT Early Childhood Education (ECE) represents a crucial stage in supporting children’s physical, cognitive, social, and emotional development, thereby requiring high-quality institutional management, including financial management. Transparent and accountable financial governance remains a major challenge for ECE institutions in maintaining the sustainability of educational services and strengthening public trust. This study aims to evaluate innovative approaches to financial management in ECE institutions based on Good Financial Governance principles to enhance institutional transparency and accountability. The study employed a qualitative approach through a literature review by analyzing various relevant scientific sources related to educational financial management. The findings indicate that the implementation of Good Financial Governance can be achieved through participatory budgeting, the utilization of technology in financial management, the presentation of accessible financial reports, the establishment of professional financial teams, and well-directed and sustainable fund management. The novelty of this study lies in emphasizing the integration of Good Financial Governance principles with innovative financial management practices in ECE institutions as a strategy to improve educational service quality. The conclusion confirms that the implementation of sound financial governance enhances transparency, accountability, and community participation, thereby supporting the sustainable improvement of ECE service quality. ABSTRAK Pendidikan Anak Usia Dini (PAUD) merupakan fase penting dalam mendukung perkembangan fisik, kognitif, sosial, dan emosional anak sehingga memerlukan pengelolaan lembaga yang berkualitas, termasuk dalam aspek keuangan. Pengelolaan keuangan yang transparan dan akuntabel menjadi tantangan bagi lembaga PAUD dalam menjaga keberlanjutan layanan pendidikan serta meningkatkan kepercayaan masyarakat. Penelitian ini bertujuan untuk mengevaluasi pendekatan inovatif dalam pengelolaan keuangan PAUD berbasis prinsip Good Financial Governance guna memperkuat transparansi dan akuntabilitas lembaga. Penelitian menggunakan pendekatan kualitatif melalui studi kepustakaan dengan menganalisis berbagai literatur ilmiah yang relevan terkait manajemen keuangan pendidikan. Hasil penelitian menunjukkan bahwa penerapan Good Financial Governance dapat diwujudkan melalui penyusunan anggaran partisipatif, pemanfaatan teknologi dalam pengelolaan keuangan, penyajian laporan keuangan yang mudah dipahami, pembentukan tim keuangan yang profesional, serta pengelolaan dana yang terarah dan berkelanjutan. Novelty penelitian ini terletak pada penekanan integrasi prinsip Good Financial Governance dengan inovasi pengelolaan keuangan PAUD sebagai strategi peningkatan mutu layanan pendidikan. Simpulan penelitian menegaskan bahwa penerapan tata kelola keuangan yang baik mampu meningkatkan transparansi, akuntabilitas, dan partisipasi masyarakat sehingga mendukung peningkatan kualitas layanan PAUD secara berkelanjutan.